Going Public '05 : From the Balkans to the Baltic. - Mircan, Mihnea; Cichocki, Sebastian; Domela, Paul; Boeri, Stefano; Sierakowski, Slawomir; Zanfi, Claudia; Oroveanu, Mihai; Costinas, Cosmin; Szylak, Aneta; Manovich, Lev; Tiron, Stefan; Lootsma, Bart; et al. (Milano : Silvana Editoriale, 2005)
Vaccari, Franco ; Braila, Pavel ; Atlhamer, Pawel ; Ion, Razvan ; Stanciulescu, Bogdan ; Cantor, Mircea ; Muresan, Ciprian ; Vanga, Gabriela ; Klaman, Grzegorz ; Biemann, Ursula ; Atelier van Lieshout ; et al.
Modena e Formigine, 115 ottobre - 30 novembre 2005
kunstcatalogus
Keywords: Balkan